Dual function of active constituents from bark of Ficus racemosa L in wound healing - Nisansala Swarnamali Bopage; G. M. Kamal Bandara Gunaherath; Kithsiri Hector Jayawardena; Sushila Chandrani Wijeyaratne; Ajita Mahendra Abeysekera; Seneviratne Somaratne (BMC, 2018)
Abstract Background Different parts including the latex of Ficus racemosa L. has been used as a medicine for wound healing in the Ayurveda and in the indigenous system of medicine in Sri Lanka. This plant has been evaluated for its wound healing potential using animal models. The aim of this study was to obtain an insight into the wound healing process and identify the potential wound healing active substance/s present in F. racemosa L. bark using scratch wound assay (SWA) as the in-vitro assay method. Method Stem bark extracts of F. racemosa were evaluated using scratch wound assay (SWA) on Baby Hamster Kidney (BHK 21) and Madin-Darby Canine Kidney (MDCK) cell lines and Kirby Bauer disc diffusion assay on common bacteria and fungi for cell migration enhancing ability and antimicrobial activity respectively. Dichloromethane and hexanes extracts which showed cell migration enhancement activity on SWA were subjected to bioactivity directed fractionation using column chromatography followed by preparative thin layer chromatography to identify the compounds responsible for the cell migration enhancement activity. Results Dichloromethane and hexanes extracts showed cell migration enhancement activity on both cell lines, while EtOAc and MeOH extracts showed antibacterial activity against Staphylococcus and Bacillus species and antifungal activity against Saccharomyces spp. and Candida albicans. Lupeol (1) and β-sitosterol (2) were isolated as the potential wound healing active compounds which exhibited significant cell migration enhancement activity on BHK 21 and MDCK cell lines (> 80%) in par with the positive control, asiaticoside at a concentration of 25 μM. The optimum concentration of each compound required for the maximum wound healing has been determined as 30 μM and 35 μM for 1 and 2 respectively on both cell lines. It is also established that lupeol acetate (3) isolated from the hexanes extract act as a pro-drug by undergoing hydrolysis into lupeol in the vicinity of cells. Conclusion Different chemical constituents present in stem bark of Ficus racemosa L show enhancement of cell migration (which corresponds to the cell proliferation) as well as antimicrobial activity. This dual action of F. racemosa stem bark provides scientific support for its traditional use in wound healing.